2020
DOI: 10.1007/s11071-019-05462-z
|View full text |Cite
|
Sign up to set email alerts
|

Solution and asymptotic analysis of a boundary value problem in the spring–mass model of running

Abstract: We consider the classic spring-mass model of running which is built upon an inverted elastic pendulum. In a natural way, there arises an interesting boundary value problem for the governing system of two nonlinear ordinary differential equations. It requires us to choose the stiffness to ascertain that after a complete step, the spring returns to its equilibrium position. Motivated by numerical calculations and real data we conduct a rigorous asymptotic analysis in terms of the Poicaré-Lindstedt series. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The same approximation of K as ( 27) was obtained in [27] and [29]. Moreover, in [28] it was shown that the leading order of the expansion of…”
Section: Symmetric Solutionssupporting
confidence: 69%
See 4 more Smart Citations
“…The same approximation of K as ( 27) was obtained in [27] and [29]. Moreover, in [28] it was shown that the leading order of the expansion of…”
Section: Symmetric Solutionssupporting
confidence: 69%
“…An asymptotic analysis of the main equations (2) with the use of the Poincaré -Lindstedt series was carried out in [27]. The solution of the problem is based on the perturbative expansion related to the significant spring stiffness (K → ∞).…”
Section: Constructing Approximate Solutionsmentioning
confidence: 99%
See 3 more Smart Citations